(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Ad hoc networks networks have been serving us in for sure, for a considerable length of time, through their huge assortment of applications in greater part fields. Because of their elements like threatening arrangements, elevated degree of versatility, restricted assets and actual uncertainty, they are in cutting edge to assailants. First line of protection (cryptographic procedures, fire walls and so forth) shuts down these assaults. As the recent denial-of-service attacks on several major Internet sites have shown us, no open computer network is immune from intrusions. The wireless ad-hoc network is particularly vulnerable due to its features of open medium, dynamic changing topology, cooperative algorithms, lack of centralized monitoring and management point, and lack of a clear line of defense. Many of the intrusion detection techniques developed on a fixed wired network are not applicable in this new environment. How to do it differently and effectively is a challenging research problem. In this paper, we first examine the vulnerabilities of a wireless ad-hoc network, the reason why we need intrusion detection, and the reason why the current methods cannot be applied directly. We then describe the new intrusion detection and response mechanisms that we are developing for wireless ad-hoc networks.